Reliability and Validity of the Upper-body Dressing Scale in Japanese Patients with Vascular Dementia with Hemiparesis. - Endo, Arisa; Suzuki, Makoto; Akagi, Atsumi; Chiba, Naoyuki; Ishizaka, Ikuyo; Matsunaga, Atsuhiko; Fukuda, Michinari (Occupational Therapy International, 2015)
The purpose of this study was to examine the reliability and validity of the Upper-body Dressing Scale (UBDS) for buttoned shirt dressing, which evaluates the learning process of new component actions of upper-body dressing in patients diagnosed with dementia and hemiparesis. This was a preliminary correlational study of concurrent validity and reliability in which 10 vascular dementia patients with hemiparesis were enrolled and assessed repeatedly by six occupational therapists by means of the UBDS and the dressing item of the Functional Independence Measure (FIM). Intraclass correlation coefficient was 0.97 for intra-rater reliability and 0.99 for inter-rater reliability. The level of correlation between UBDS score and FIM dressing item scores was −0.93. UBDS scores for paralytic hand passed into the sleeve and sleeve pulled up beyond the shoulder joint were worse than the scores for the other components of the task. The UBDS has good reliability and validity for vascular dementia patients with hemiparesis. Further research is needed to investigate the relation between UBDS score and the effect of intervention and to clarify sensitivity or responsiveness of the scale to clinical change. Copyright © 2014 John Wiley & Sons, Ltd.